PENERAPAN PERILAKU JUJUR MELALUI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Awalia Marwah Suhandi; Dinie Anggraeni Dewi; Yayang Furi Furnamasari (Academy of Education Journal, 2022)
Honest behavior is the key to better education. In this case, education seems to turn a deaf ear to various problems related to honest problems. For that we need a solution to minimize it. A strategic solution to overcome these problems is to carry out civic education learning in elementary schools. The purpose of this research is to apply honest living behavior through civic education learning in elementary schools. In this case, civics education learning in elementary schools is important to be held because it will form a character attitude for students. Meanwhile, this study uses a qualitative method by conducting a literature study on the opinions of the figures and reviewing journals related to the material. The conclusion of this study is that civic education in elementary schools makes students good citizens because the content of the learning materials taught contains the value of character education, one of which is honest behavior.